2022
DOI: 10.7324/japs.2022.120619
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cardamom (Amomum compactum) fruit extraction using the Box–Behnken design focused on polyphenol extraction with antioxidant activity

Abstract: Cardamom, known by the scientific name Amomum compactum, is a plant from the Zingiberaceae family that contains various phytochemical compounds such as polyphenols and alkaloids, which have pharmacological treatment activity. Based on previous studies, cardamom fruit extraction has never been optimized to determine its bioactivity as an antioxidant. Therefore, this research aims to acquire extraction optimization conditions, including solvent ratio, ethanol concentration, and extraction time of the overall phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Cardamom seed contains secondary metabolites that are pharmacologically efficacious. Some secondary metabolites reported in cardamom are phenolic and flavonoids compounds, which are used as antioxidants (Juliana et al, 2022;Ballard et al, 2018). These compounds can be isolated from cardamom seeds by extraction.…”
Section: Total Phenol and Total Flavonoids Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Cardamom seed contains secondary metabolites that are pharmacologically efficacious. Some secondary metabolites reported in cardamom are phenolic and flavonoids compounds, which are used as antioxidants (Juliana et al, 2022;Ballard et al, 2018). These compounds can be isolated from cardamom seeds by extraction.…”
Section: Total Phenol and Total Flavonoids Propertiesmentioning
confidence: 99%
“…These compounds can be isolated from cardamom seeds by extraction. Extraction is important in recovering phenolic and flavonoid compounds, which is influenced by several factors such as type of solvent (Qomaliyah et al, 2019) and extraction time (Soos et al, 2019;Juliana et al, 2022).…”
Section: Total Phenol and Total Flavonoids Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the process is subject to various factors such as the choice of extraction solvents, the ratio of sample to solvent, the duration and method of extraction, as well as the physical and chemical characteristics of the sample matrix. [15][16][17] The existing research does not present a consensus regarding a singular, effective standard extraction procedure or the optimal extraction solvent. Multiple studies have found that solid-liquid extraction employing various solvents is the most efficient method, with solvents of higher polarity often exhibiting enhanced solubility of polyphenols in the extraction process.…”
mentioning
confidence: 99%